The Influence of Strategic Leadership and the Role of Conflict on Turnover Intention Mediated by Work Stress on Employees of Muhammad Ali Kasim Regional General Hospital, Gayo Lues Regency - Monalisa Kurnia P; Sayed Mahdi; Meutia Dwi Novita Sari (International Journal of Kita Kreatif, 2026)
The purpose of this study is to analyze The influence of strategic leadership and the role of conflict on turnover intention mediated by work stress on employees of Muhammad Ali Kasim Regional General Hospital, Gayo Lues Regency. The number of respondents in the study was 76 employees at Muhammad Ali Kasim Regional General Hospital, Gayo Lues Regency. The sampling technique used was purposive sampling with a non-probability sampling method. In accordance with data availability and analysis demands, the researcher used SPSS version 24 to analyze the data. This study suggests that not all variables have a significant effect between direct and mediation relationships starting from strategic leadership does not affect work stress, the role of conflict affects work stress, strategic leadership does not affect turnover intention, the role of conflict and work stress affect turnover intention. Then work stress is not able to mediate the relationship between strategic leadership on turnover intention and work stress is able to mediate the relationship between the role of conflict on turnover intention at Muhammad Ali Kasim Regional General Hospital, Gayo Lues Regency.